Ultrasound evaluation of the enteric duplication cyst: the gut signature - Di Serafino, Marco (J Ultrasound, 2015)
Gastrointestinal duplication cyst is a rare congenital anomaly that may occur anywhere along the gastrointestinal tract from the tongue to the anus. Such cysts occur most commonly in the small bowel and about half are in the mesenteric border of the ileum. Such cystic duplications communicate only rarely with the intestinal lumen although the cysts are attached to the intestine and may even share a common wall with the adjacent alimentary tract. These lesions can vary in shape, being cystic or tubular, and often show the same structure of the adjacent normal bowel. It is usually asymptomatic and complications are rare but they may include obstruction by volvulus or intussusception, bleeding, infection, and perforation. When diagnosed these lesions should be surgically resected to avoid future possible complications. The authors present a case of enteric cystic duplication and its ultrasound appearance in a 12-month-old Caucasian female infant cause of acute abdominal pain and intestinal obstruction, thus requiring urgent surgery.